Consequences of subchronic exposure to ethanolic extract from fruits and leaves of Schinus molle var. areira L. in mice - Bras, Cristina Liliana (2010)
Aim of the study: Several extracts of Schinus molle var. areira L. plant proved to be useful for the treatment of different pathologies and for the control of insect pest. Due to these potential uses, it is necessary to study their safety. In this work, we evaluated the effects of subchronic exposure to ethanolic extracts from leaves and fruits of Schinus molle var. areira in mice. Materials and methods: The plant extract was added to the diet at 1. g/kg. body weight/day for 90 days. At the end of the exposure, behavioral and functional parameters in a functional observational battery and motor activity in an open field were assessed. Finally, several biochemical and histopathological studies were realized. Results: The exposure to extract from leaves produced an increase in the number of rearings in the open field and of urine pools in the functional observational battery. On the other hand, the exposure to extract from fruits produced an increase in the neutrophil count and a decrease in the lymphocyte count and in the total cholesterol levels. None of the exposures affected the different organs evaluated. Conclusions: Our results suggest that subchronic exposure to ethanolic extracts from leaves and fruits of Schinus molle var. areira should be potentially useful in the treatment of lipid pathologies and safe to use.